Genome-Wide Identification and Characterization of Heat Shock Proteins in the Stored-Product Pest Rhyzopertha dominica (Fabricius): Phylogenetic, Structural, and Stress-Induced Expression Analyses - Yueliang Bai; Yanzhu Xie; Junji Yao; Fangfang Zeng; Dianxuan Wang (Insects)
Heat shock proteins (HSPs) are crucial molecular chaperones that help organisms maintain protein stability under stress conditions. As a major stored-product pest, Rhyzopertha dominica (Fabricius) faces distinct stresses compared to field insects, primarily due to the specific pest control methods applied during grain storage. In this study, a total of 53 HSP genes from five gene families (HSP90, HSP70, HSP60, sHSP, and DnaJ) were identified and characterized using bioinformatics methods. Among them, DnaJ was the largest and the most diverse HSP family in R. dominica. Transcriptome sequencing and RT-qPCR were then used to evaluate HSP gene expression patterns under four storage-related stresses, following a series of bioassays. Extreme high temperature was the strongest inducer of HSP expression, with 12 genes showing over a 10-fold increase. Controlled nitrogen atmosphere also led to considerable upregulation of HSP genes, especially in the HSP70 family. In contrast, phosphine fumigation and K-Obiol grain protectant caused very limited induction of HSP genes, which might have been due to the less severe protein damage caused by chemical stresses compared to physical stresses. Our study provides a theoretical basis for further research on HSP functions in R. dominica.